Enhancing Psychological Sexual Health of People With Spinal Cord Injury and Their Partners in an Italian Unipolar Spinal Unit: A Pilot Data Study - Federici, Stefano; Artegiani, Francesco; Pigliautile, Martina; Antonelli, Paolo; Diotallevi, Daniele; Ritacco, Innocenza; Maschke, Renée (Frontiers in Psychology, 2019)
Like the slogan of the American Consortium for Spinal Cord Medicine says, “No injury, no matter how serious, can take away your ability to have a relationship, experience love, and experience the attraction between two people.” However, people with spinal cord injury (SCI) have to fight with their own and societal attitudes and stereotypes that limit sexuality to the physiological functions of genitalia, phallocentric primacy of sexual pleasure, and sexual attractiveness of perfect bodies. The scope of the present study is to evaluate the impacts of a psychoeducational intervention in a personal growth group on the sexual life of seven people with SCI and four of their partners particularly their sexual interest and satisfaction, depression, and anxiety. Due to the small samples size, nonparametric statistical tests were used to compare pre- and post-outcome measures for all participants: patients and the partners group. Possible effects of gender were also considered. The effectiveness of the psychoeducational intervention was clearly apparent, showing a high effect size in improving sexual interest and satisfaction, and the opportunity and ability to enjoy sexuality. A reduction of anxiety was also observed for all participants, although it may not have been related to the psychoeducational intervention. Moreover, the intervention significantly improved the opportunity and ability to enjoy sexuality for the partner and patient group. No effect was found on depression. This was the first initiative in Italy aiming to address the sexual life and not only to cure the sexual dysfunction of people with SCI. The positive, clear evidence of the validity of the Love & Life project’s intervention bodes well for new psychoeducational initiatives that in Italy meet the sexual needs of people with SCI and their partners, providing adequate education and psychological support, involving partners, and creating a space to talk among peers.